Предмет: Математика,
автор: марина1288
4(0,6-0,3)-3(0,7x-0,1)=0
Ответы
Автор ответа:
0
4*(0,6-0,3)-3*(0,7х-0,1)=0
4*0,6-4*0,3-3*0,7х+3*0,1=0
2,4-1,2-2,1х+0,3=0
-2,1х=1,5
х=1,5/(-2,1)
х=-15/21
х=-5/7
Ответ : х= - 5/7
4*0,6-4*0,3-3*0,7х+3*0,1=0
2,4-1,2-2,1х+0,3=0
-2,1х=1,5
х=1,5/(-2,1)
х=-15/21
х=-5/7
Ответ : х= - 5/7
Похожие вопросы
Предмет: Математика,
автор: ii0745683
Предмет: Алгебра,
автор: tehelpplls
Предмет: Физика,
автор: yaaollyaa
Предмет: История,
автор: cat206
Предмет: Алгебра,
автор: Аноним